Let There Be Light-Digital Eye Strain (DES) in Children as a Shadow Pandemic in the Era of COVID-19: A Mini Review - Sudip Bhattacharya; Petra Heidler; Petra Heidler; Sheikh Mohd Saleem; Roy Rillera Marzo; Roy Rillera Marzo (Frontiers Media S.A., 2022)
IntroductionDigital eye strain, which is often ignored by the public, has emerged as a "Shadow Pandemic" in the era of the COVID-19 pandemic.AimThe current paper is aimed at discussing the ill effect of digital screens on eyes in the wake of the COVID-19 pandemic.MethodologyA literature search was done using "PubMed," "Google scholar", and "Scopus" using key terms like "Digital Eye Strain," "Eyestrain," or "Computer Vision Syndrome." Relevant articles were identified and included to support the argument for this narrative review.ResultsStudies conducted in the UK reported that 68% of children extensively use computers, while 54% undertake online activities after the age of 3. Similar studies estimated 4 h and 45 min per day of screen exposure time among adults in the UK. Indian studies reveal that the prevalence of DES is 69% in adults and 50% in children respectively. Indian ophthalmologists found that computer-using and specialized ophthalmologists were more informed of symptoms and diagnostic signs but were misinformed about treatment modalities. The use of social media and multitasking is particularly prominent among younger adults, with 87% of individuals aged 20-29 years reporting the use of two or more digital devices simultaneously. It has been observed that the use of computer glasses corrects refractive errors and helps in the reduction of symptoms, while precision spectral filters help in reducing symptoms of micro-fluctuation of accommodation.ConclusionWe concluded that DES is emerging globally as a "Shadow Pandemic" and it is high time to respond. Community ophthalmologists, public health authorities, and educational sectors especially should be involved to prevent this.